If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying X + sqrt(3) + 3x = 18 + -2x Reorder the terms for easier multiplication: X + 3qrst + 3x = 18 + -2x Solving X + 3qrst + 3x = 18 + -2x Solving for variable 'X'. Move all terms containing X to the left, all other terms to the right. Add '-3qrst' to each side of the equation. X + 3qrst + -3qrst + 3x = 18 + -3qrst + -2x Combine like terms: 3qrst + -3qrst = 0 X + 0 + 3x = 18 + -3qrst + -2x X + 3x = 18 + -3qrst + -2x Add '-3x' to each side of the equation. X + 3x + -3x = 18 + -3qrst + -2x + -3x Combine like terms: 3x + -3x = 0 X + 0 = 18 + -3qrst + -2x + -3x X = 18 + -3qrst + -2x + -3x Combine like terms: -2x + -3x = -5x X = 18 + -3qrst + -5x Simplifying X = 18 + -3qrst + -5x
| 15.4*4.75= | | 6c-3-2c=4c+4-0 | | -6+3(1+v)=5+5v | | (a-2b)(a+2b)=45 | | -b^2-9= | | 420-3x=4x | | 4xn+11=27 | | 60x=5x+1 | | 2[2x-1]=-14 | | 1x+9=16 | | 0.125(6+x)=8 | | 2[2x-1]=14 | | 5(b-5)=-15-5b | | x^2+2-3-y=0 | | .333333x+0=1017 | | Z^2=-49 | | 15=2(2x+9)-x | | -(x-1)=-3(2x+3) | | 3(x-5)-48=2(x-8) | | Y^2=2.77 | | .25x+0=866 | | 1xn+13=17 | | -2[3x+9]=18 | | 16w-20y=24 | | 3x+2(2x-2)=31 | | 3x+2y-2=0 | | -(x-1)=-3-2(3x+3) | | -20+4r=4+4(2+5r) | | .333333x+0=.25x+0 | | 3x-4(5-x)=7x+2 | | -2[3x-9]=18 | | 12x-x-12=x-2 |